2023
DOI: 10.1136/bmj-2022-073923
|View full text |Cite|
|
Sign up to set email alerts
|

Pathophysiology, diagnosis, and management of neuroinflammation in covid-19

Rachel L Brown,
Laura Benjamin,
Michael P Lunn
et al.

Abstract: Although neurological complications of SARS-CoV-2 infection are relatively rare, their potential long term morbidity and mortality have a significant impact, given the large numbers of infected patients. Covid-19 is now in the differential diagnosis of a number of common neurological syndromes including encephalopathy, encephalitis, acute demyelinating encephalomyelitis, stroke, and Guillain-Barré syndrome. Physicians should be aware of the pathophysiology underlying these presentations to diagnose and treat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 182 publications
(346 reference statements)
0
7
0
Order By: Relevance
“…Despite our humanized hACE2ki mouse line not displaying severe disease progression when inoculated with various SARS‐CoV‐2 variants at a young adult age, we aimed to assess its suitability for investigating long‐COVID or post‐acute sequelae of SARS‐CoV‐2 infection pathogenesis and potential interventions. A key focus was to determine if SARS‐CoV‐2 infection in this model leads to tau pathologies, a known indicator for neurological disorders and a suggested long‐term consequence of SARS‐CoV‐2 infection 8–13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite our humanized hACE2ki mouse line not displaying severe disease progression when inoculated with various SARS‐CoV‐2 variants at a young adult age, we aimed to assess its suitability for investigating long‐COVID or post‐acute sequelae of SARS‐CoV‐2 infection pathogenesis and potential interventions. A key focus was to determine if SARS‐CoV‐2 infection in this model leads to tau pathologies, a known indicator for neurological disorders and a suggested long‐term consequence of SARS‐CoV‐2 infection 8–13 …”
Section: Resultsmentioning
confidence: 99%
“…suggested long-term consequence of SARS-CoV-2 infection. [8][9][10][11][12][13] Recent investigations have revealed increased hyperphosphorylated tau181 (p-tau181) in individuals afflicted with SARS-CoV-2 infection 14 and during the convalescence phase following COVID-19 infection. 15 This particular variant of hyperphosphorylated tau 181 has been identified as a specific biomarker associated with AD.…”
Section: Differential Host Immune Responses In Hace2ki Mice To Sars-c...mentioning
confidence: 99%
“…Several studies reported signs of neuroinflammation in tissue from COVID-19 patients (reviewed by (Almutairi et al, 2021; Brown et al, 2023; Gonçalves de Andrade et al, 2021; Hernández-Parra et al, 2023; Iadecola et al, 2020; Natale, Lukens, & Petri, 2022; Tremblay et al, 2020; Vanderheiden & Klein, 2022; A. C. Yang et al, 2021)). SARS-CoV-2 not only infects the respiratory tract but also other organs, including the brain and its cerebrovasculature (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cytokines are interleukin 2R, interleukin 6, interleukin 8, tumor necrosis factor (TNF, also known as TNF-alpha) and, interestingly, also the anti-inflammatory interleukin-10 (Devlin & Gombolay, 2023; Liu et al, 2020). Macrophages and lymphocytes penetrate the blood-brain barrier, activate microglial cells and astrocytes and finally determine neuroinflammation (Almutairi et al, 2021; Brown et al, 2023; Gonçalves de Andrade et al, 2021; Hernández-Parra et al, 2023; Iadecola et al, 2020; Tremblay et al, 2020; Vanderheiden & Klein, 2022). In our study, both microglial cells and astrocytes showed an activated phenotype in COVID-19 patients, confirming neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation